The stone Gods - Winterson, Jeanette (Penguin Books, 2008)
On the airwaves, all the talk is of the new blue planet, pristine and habitable, like our own was 65 million years ago, before we took it to the edge of destruction. Off the air, Billie Crusoe and the renegade robo-sapian Spike are falling in love. Along with Captain Handsome and Pink, they're assigned to colonize the new blue planet. But when a technical maneuver intended to make it inhabitable backfires, Billie and Spike's flight to the future becomes a surprising return to the distant past. "Everything is imprinted forever with what it once was." What will happen when their story combines with the world's story' Will they -- and we -- ever find a safe landing place'Playful, passionate, polemical, and frequently very funny, The Stone Gods will change forever the stories we tell about the earth, about love, and about stories themselves.